Financial and Digital Literacy: Their Impact on Interest Use of QRIS and Entrepreneurial Behavior - anggraeni, oki; Puspasari, Elsa; Ilma, Ajeng Faizah Nijma; Fatimah, Siti (EconBank: Journal of Economics and Banking, 2025)
The Quick Response Code Indonesia Standard QRIS service has supported payments from bank and non-bank providers used in the community. This payment system through QRIS can not only be done in malls or large shopping centers but can also be used in stalls, tourist attractions, even traditional markets or traditional markets if they already use the QRIS logo. Pasar Manis Purwokerto was the location of the study with 49 respondents. The analysis technique used was multiple linear regression analysis. The results of the study showed that financial literacy, digital literacy and the use of the QRIS application had a positive and significant influence on entrepreneurial behavior. Digital literacy is the most dominant variable in influencing entrepreneurial behavior in the Pasar Manis Purwokerto.